PENGARUH PEMASARAN RELASIONAL TERHADAP LOYALITAS (Studi pada Anggota Koperasi Simpan Pinjam Coblong Pamor di Denpasar) - I Dewa Gede Kresna Wirawan; Putu Siti Firmani (Widyadari : Jurnal Pendidikan, 2021)
The purpose of this study was to examine the effect of relationship marketing on the loyalty of members of the Coblong Pamor Savings and Loans Cooperative. Testing the research hypothesis using the SPSS method with a sample of 70 people who live in Denpasar. Determination of the sample using probability sampling method with the technique of proportionate stratified random sampling, where this technique is used if the population has members or elements that are not homogeneous and proportionally stratified, with the criteria of respondents who have made transactions during the last 3 years. The findings in this study indicate that member trust, member communication and member commitment have a positive and significant effect on member loyalty partially or simultaneously. This research has the implication that it is important for management to improve relational relationships through trust, communication and commitment so that members become loyal to the Coblong Pamor Cooperative.